Food Fortification in India: A Literature Review - Liu, Pam; Bhatia, Rita; Pachón, Helena; ., Emory (Indian Journal of Community Health, 2014)
Background: India has a high prevalence of micronutrient deficiency-related health risks, which can be improved by food fortification. Objectives: To identify and analyze single or multiple micronutrient (MMN) food-fortification studies for their efficacy and effectiveness in India. Methods: Papers from searching 10 databases were independently screened by two researchers. Data were abstracted to summarize food fortification results on biological markers, anthropometry, clinical, morbidity, cognition, dietary intake, and physical performance. Results: Forty-seven papers, of which 25 were randomized controlled trials, were included for analysis. Children ?12 y were the main population (n=38). Food vehicles were cereals (n=6), oils and salts (n=18), and other (e.g., school meals (n=23)). Improvements in ?1 biological markers were reported in all 35 papers (22 MMN, 9 Iron, 4 Iodine) with interpretable results. More specifically, iron or hemoglobin improvements were noted in all papers fortifying with MMN or solely iron. Iodine nutriture was improved in all salt iodization papers. Eight of 14, 6 of 7, 2 of 6, 4 of 6, 1 of 4, and 1 of 1 papers with interpretable results showed ?1 positive result of fortification in anthropometry, clinical signs, morbidity, cognition, dietary intake, and physical performance, respectively. Conclusion: Research in India suggests food fortification improves biological markers, particularly iron and hemoglobin when fortifying with MMN or iron. MMN fortification saw more health impacts than using single fortificants. Iodine status was improved through salt iodization. Existing government nutrition programs, especially those that target children, are good avenues for food fortification implementation.